2011
DOI: 10.3109/02770903.2011.637595
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Self-Management is Sub-Optimal in Urban Hispanic and African American/Black Early Adolescents with Uncontrolled Persistent Asthma

Abstract: Introduction Youth as young as 11 are given responsibility to manage their asthma. Yet, little is known regarding early adolescents’ asthma self-management behaviors. This study characterizes urban early adolescents’ asthma self-management behaviors and perceived responsibility to manage asthma, exploring demographic differences and examining the relationship between asthma responsibility and disease management. Methods 317 Hispanic and Black early adolescents (mean age=12.7) with persistent, uncontrolled as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 36 publications
1
69
0
Order By: Relevance
“…Although aware of the need to assume greater responsibility for their asthma care, in this study adolescents still needed reminders or directions from caregivers regarding carrying rescue inhalers, getting prescriptions refilled, or taking action when asthma symptoms arise. Bruzzese et al (2012) findings indicated deficiencies and discrepancies among youth in their response to acute asthma symptoms, administering medications prior to exposure to known triggers, and remembering to carry medications when outside the home. The same investigators also found that as youth grew older, asthma self-management often declined.…”
Section: Discussionmentioning
confidence: 93%
“…Although aware of the need to assume greater responsibility for their asthma care, in this study adolescents still needed reminders or directions from caregivers regarding carrying rescue inhalers, getting prescriptions refilled, or taking action when asthma symptoms arise. Bruzzese et al (2012) findings indicated deficiencies and discrepancies among youth in their response to acute asthma symptoms, administering medications prior to exposure to known triggers, and remembering to carry medications when outside the home. The same investigators also found that as youth grew older, asthma self-management often declined.…”
Section: Discussionmentioning
confidence: 93%
“…The second study, which was based on electronic monitoring of adherence, showed lower adherence in children with more responsibility [21]. In contrast to common belief [16], children below the age of 10-12 years seem to be unable to take responsibility for their own taking of medicine [33,34]. To identify and overcome this barrier to adherence, parental beliefs about the self-management responsibility of their child should be discussed during follow-up visits, along with the associated lack of motivation to achieve good adherence and ineffective problem-solving behavior.…”
Section: Discussionmentioning
confidence: 97%
“…Despite huge progress in asthma management over the last decades, sat isfactory levels of asthma control are not univer sal. 11,12 Apart from the few truly refractory cases, failure to achieve or maintain optimal control has been attributed to inappropriate dosing or drug selection, patient noncompliance, or deficient in haler technique. [12][13][14][15] It remains an important is sue because suboptimal levels of asthma control are a risk factor for asthma exacerbations.…”
Section: 3-59mentioning
confidence: 99%